Phase determination using chromosomal microarray and fluorescence in situ hybridization in a patient with early onset Parkinson disease and two deletions in PRKN. Issue 3 (25th March 2018) - Williams, Eli S.; Barrett, Matthew J.; Dhamija, Radhika; Toran, Lisa; Chambers, Chelsea; Mahadevan, Mani S.; Golden, Wendy L.
Abstract: Background: Mutations in the parkin gene ( PRKN ) are the most commonly identified genetic factors in early onset Parkinson disease (EOPD), with biallelic mutations, resulting in a clinical phenotype. However, normal variation is also common in PRKN, particularly in the form of copy number variation (CNV), challenging interpretation of genetic testing results. Here we report a case of a 29‐year‐old male with EOPD and two deletions in PRKN detected by chromosomal microarray (CMA). Methods: The proband was clinically examined by a neurologist for postural instability with frequent falls, bradykinesia, gait freezing with festination, and hypophonia. Chromosomal microarray analysis (CMA) was performed on the proband and his parents using the Affymetrix CytoScan HD microarray. Subsequent fluorescence in situ hybridization (FISH) was performed on the proband and both parents. Results: Chromosomal microarray detected the presence of two deletions of PRKN in the proband. Parental CMA analysis was performed to determine the clinical significance of this finding, as well as to demonstrate phase of these deletions. Parental CMA revealed that one deletion was paternally inherited and one deletion was de novo. A custom FISH approach was then successfully used to phase the deletions. Conclusion: Chromosomal microarray and fluorescence in situ hybridization analysis of this trio identified two deletions in PRKN occurring in trans, providing a genetic etiology for the clinical diagnosis of EOPD. The determination of inheritance and phase of the deletions was critical to the proper interpretation of these results. These findings highlight the utility of CMA in the detection of clinically relevant CNVs in cases of EOPD, and also serve to emphasize the importance of follow‐up FISH and parental testing. Abstract : Biallelic mutations and deletions of PRKN result in early onset Parkinson disease. This case report demonstrates the utility of CMA in EOPD diagnosis and also serves to emphasize the importance of follow‐up FISH and parental testing.